Interactions Between Weight Loss and Plasma Neurodegenerative Markers for Determining Cognitive Decline Among Community-Dwelling Older Adults. Issue 6 (16th January 2022) - Giudici, Kelly Virecoulon; Guyonnet, Sophie; Morley, John E; Nguyen, Andrew D; Aggarwal, Geetika; Parini, Angelo; Li, Yan; Bateman, Randall J; Vellas, Bruno; de Souto Barreto, Philipe; ,
Abstract: This study aimed to investigate the interaction between weight loss (WL) and plasma amyloid-β 42/40 (Aβ 42/40 ), neurofilament light chain (NfL), progranulin, and their association with cognitive decline over time among older adults. This 5-year observational approach included 470 participants from the Multidomain Alzheimer Preventive Trial, mean age 76.8 years ( SD = 4.5), 59.4% women. WL was defined as ≥5% decrease over the first year. Biomarkers were measured at 12 months. Cognitive function was assessed yearly from 12 months onward by Mini-Mental State Examination (MMSE); Clinical Dementia Rating sum of boxes (CDR-SB); a composite score based on Category Naming Test; Digit Symbol Substitution Test; 10 MMSE orientation items (MMSEO) and free and total recall of the Free and Cued Selective Reminding test; and these tests individually. Twenty-seven participants (5.7%) presented WL. In adjusted analyses, combined WL + lower Aβ 42/40 (≤0.103, lowest quartile) was related with more pronounced 4-year cognitive decline according to CDR-SB ( p < .0001) and MMSEO ( p = .021), compared with non-WL + higher Aβ 42/40 . WL + higher NfL (>94.55 pg/mL, highest quartile) or progranulin (>38.4 ng/mL, 3 higher quartiles) were related with higher cognitive decline according to CDR-SB, MMSE, MMSEO, and composite score (all p < .03), compared with non-WL + lower NfL or higher progranulin. Regrouping progranulin quartiles (Q1–Q3 vs Q4) revealed higher cognitive decline among the WL + lower progranulin group compared with non-WL + lower progranulin. In conclusion, 1-year WL was associated with subsequent higher 4-year cognitive decline among older adults presenting low Aβ 42/40 or high NfL. Future studies combining plasma biomarker assessments and body weight surveillance may be useful for identifying people at risk of cognitive impairment. Clinical trial number: NCT00672685.